Answer:
![cos(\alpha+\beta)=-\frac{84}{85}](https://tex.z-dn.net/?f=cos%28%5Calpha%2B%5Cbeta%29%3D-%5Cfrac%7B84%7D%7B85%7D)
Step-by-step explanation:
we know that
![cos(\alpha+\beta)=cos(\alpha)*cos(\beta)-sin(\alpha)*sin(\beta)](https://tex.z-dn.net/?f=cos%28%5Calpha%2B%5Cbeta%29%3Dcos%28%5Calpha%29%2Acos%28%5Cbeta%29-sin%28%5Calpha%29%2Asin%28%5Cbeta%29)
Remember the identity
![cos^{2} (x)+sin^2(x)=1](https://tex.z-dn.net/?f=cos%5E%7B2%7D%20%28x%29%2Bsin%5E2%28x%29%3D1)
step 1
Find the value of ![sin(\alpha)](https://tex.z-dn.net/?f=sin%28%5Calpha%29)
we have that
The angle alpha lie on the III Quadrant
so
The values of sine and cosine are negative
![cos(\alpha)=-\frac{8}{17}](https://tex.z-dn.net/?f=cos%28%5Calpha%29%3D-%5Cfrac%7B8%7D%7B17%7D)
Find the value of sine
![cos^{2} (\alpha)+sin^2(\alpha)=1](https://tex.z-dn.net/?f=cos%5E%7B2%7D%20%28%5Calpha%29%2Bsin%5E2%28%5Calpha%29%3D1)
substitute
![(-\frac{8}{17})^{2}+sin^2(\alpha)=1](https://tex.z-dn.net/?f=%28-%5Cfrac%7B8%7D%7B17%7D%29%5E%7B2%7D%2Bsin%5E2%28%5Calpha%29%3D1)
![sin^2(\alpha)=1-\frac{64}{289}](https://tex.z-dn.net/?f=sin%5E2%28%5Calpha%29%3D1-%5Cfrac%7B64%7D%7B289%7D)
![sin^2(\alpha)=\frac{225}{289}](https://tex.z-dn.net/?f=sin%5E2%28%5Calpha%29%3D%5Cfrac%7B225%7D%7B289%7D)
![sin(\alpha)=-\frac{15}{17}](https://tex.z-dn.net/?f=sin%28%5Calpha%29%3D-%5Cfrac%7B15%7D%7B17%7D)
step 2
Find the value of ![cos(\beta)](https://tex.z-dn.net/?f=cos%28%5Cbeta%29)
we have that
The angle beta lie on the IV Quadrant
so
The value of the cosine is positive and the value of the sine is negative
![sin(\beta)=-\frac{4}{5}](https://tex.z-dn.net/?f=sin%28%5Cbeta%29%3D-%5Cfrac%7B4%7D%7B5%7D)
Find the value of cosine
![cos^{2} (\beta)+sin^2(\beta)=1](https://tex.z-dn.net/?f=cos%5E%7B2%7D%20%28%5Cbeta%29%2Bsin%5E2%28%5Cbeta%29%3D1)
substitute
![(-\frac{4}{5})^{2}+cos^2(\beta)=1](https://tex.z-dn.net/?f=%28-%5Cfrac%7B4%7D%7B5%7D%29%5E%7B2%7D%2Bcos%5E2%28%5Cbeta%29%3D1)
![cos^2(\beta)=1-\frac{16}{25}](https://tex.z-dn.net/?f=cos%5E2%28%5Cbeta%29%3D1-%5Cfrac%7B16%7D%7B25%7D)
![cos^2(\beta)=\frac{9}{25}](https://tex.z-dn.net/?f=cos%5E2%28%5Cbeta%29%3D%5Cfrac%7B9%7D%7B25%7D)
![cos(\beta)=\frac{3}{5}](https://tex.z-dn.net/?f=cos%28%5Cbeta%29%3D%5Cfrac%7B3%7D%7B5%7D)
step 3
Find cos (α + β)
![cos(\alpha+\beta)=cos(\alpha)*cos(\beta)-sin(\alpha)*sin(\beta)](https://tex.z-dn.net/?f=cos%28%5Calpha%2B%5Cbeta%29%3Dcos%28%5Calpha%29%2Acos%28%5Cbeta%29-sin%28%5Calpha%29%2Asin%28%5Cbeta%29)
we have
![cos(\alpha)=-\frac{8}{17}](https://tex.z-dn.net/?f=cos%28%5Calpha%29%3D-%5Cfrac%7B8%7D%7B17%7D)
![sin(\alpha)=-\frac{15}{17}](https://tex.z-dn.net/?f=sin%28%5Calpha%29%3D-%5Cfrac%7B15%7D%7B17%7D)
![sin(\beta)=-\frac{4}{5}](https://tex.z-dn.net/?f=sin%28%5Cbeta%29%3D-%5Cfrac%7B4%7D%7B5%7D)
![cos(\beta)=\frac{3}{5}](https://tex.z-dn.net/?f=cos%28%5Cbeta%29%3D%5Cfrac%7B3%7D%7B5%7D)
substitute
![cos(\alpha+\beta)=-\frac{8}{17}*\frac{3}{5}-(-\frac{15}{17})*(-\frac{4}{5})](https://tex.z-dn.net/?f=cos%28%5Calpha%2B%5Cbeta%29%3D-%5Cfrac%7B8%7D%7B17%7D%2A%5Cfrac%7B3%7D%7B5%7D-%28-%5Cfrac%7B15%7D%7B17%7D%29%2A%28-%5Cfrac%7B4%7D%7B5%7D%29)
![cos(\alpha+\beta)=-\frac{24}{85}-\frac{60}{85}](https://tex.z-dn.net/?f=cos%28%5Calpha%2B%5Cbeta%29%3D-%5Cfrac%7B24%7D%7B85%7D-%5Cfrac%7B60%7D%7B85%7D)
![cos(\alpha+\beta)=-\frac{84}{85}](https://tex.z-dn.net/?f=cos%28%5Calpha%2B%5Cbeta%29%3D-%5Cfrac%7B84%7D%7B85%7D)
Answer:
![m=\frac{4}{9}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B4%7D%7B9%7D)
Step-by-step explanation:
Using the slope formula:
![m=\frac{1+7}{10+8}=\frac{8}{18}=\frac{4}{9}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B1%2B7%7D%7B10%2B8%7D%3D%5Cfrac%7B8%7D%7B18%7D%3D%5Cfrac%7B4%7D%7B9%7D)
First step:
simplify the values in the parenthesis:
-4(3+11v)
Second step:
apply the distributive property:
-12-44v
The final answer (simplified) is -44v-12
Hi Student!
This question is fairly simple because it gives us an equation and they also give us a value for the variable that is within the equation and they tell us evaluate the expression. So let's plug in the values and solve.
<u>Plug in the values</u>
<u>Factor out the exponent</u>
<u>Combine</u>
Therefore, the final answer that we would get when substituting m with 9 in the given equation is that we get 86.